Ateny i Dodona w V w. p.n.e - Wolicki, Aleksander (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
This paper gives an overview of the Athenian presence at Dodona and of the Dodona’s presence in the Athenian tradition and politics. Author argues that closer relations between Athens and the oracle began later than supposed and points to the general Phormion as instrumental in building them.
Keywords: Dodona; Ateny; wyrocznie; Formion